Integrated Training Method of Decision Support System (DSS) for MSMEs and Tourism in Empowering Bumdes Towards Food Security Based on A Blue Economy (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service initiative aimed to enhance the economic resilience of Puger Kulon Village, a coastal community in Jember Regency, by implementing a digital empowerment model. The program focused on developing and deploying the E-CoDigimark platform—an integrated e-commerce and Decision Support System (DSS)—to strengthen the synergy between local Micro, Small, and Medium Enterprises (MSMEs) and the tourism sector within a blue economy framework. A Participatory Action Research (PAR) approach was adopted over six months, involving 40 participants, including BUMDes staff and MSME owners. Activities encompassed socialization, intensive digital literacy and DSS training, platform development using the Scrum SDLC model, and ongoing technical assistance. Results demonstrated a significant improvement in participants' digital capacity, with pre-test and post-test scores increasing from 48.5 to 76.8 (p < 0.01). The platform successfully onboarded 35 local products and recorded 500 visits within the first month, contributing to a 28% average increase in MSME sales and a 12% rise in tourist visits to Pancer Beach. Furthermore, 85% of participants reported actively using the DSS for weekly business decisions. The findings indicate that the DSS-based E-CoDigimark platform effectively empowers coastal communities by fostering data-driven decision-making, expanding market access, and creating a sustainable digital ecosystem that aligns with blue economy principles. This model offers a replicable strategy for enhancing rural economic resilience through integrated digital transformation.